Implications of the New Framework for Market Abuse in the EU - Čunderlík, Ľubomír (Public Governance, Administration and Finances Law Review, 2016)
The Market Abuse Regulation (MAR) was adopted in April 2014, and it has been uniformly regulating the issues of insider dealing and market manipulation throughout the EU since 3 July 2016. Unlike the previous legislation, deviation from the regulation’s wording will not be possible. This should exclude different applications, which have occurred in the individual EU Member States so far, when investigating unlawful behaviours marked as market abuse. The regulation introduced several substantial changes.